The effects of punishment on the acquisition and maintenance of reading behavior in retarded children - Ribes, Emilio; Galesso-Coaracy, Salvador A.; Duran, Lilia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The use of punishment for incorrect responding in reading by three re traded children is described. The results show positive effects of punishment in the acquisition and maintenance of reading behavior. The outcome is discussed in relation to discrimination training and a more extensive evaluation of punishment effects in academic behaviors with retarded children is suggested.